Die Vita Fursei als chronologische Quelle - Hamann, Stefanie (Analecta Bollandiana, 2004)
This paper constructs an outline biography of the seventh-century Irish saint Fursey based on the Frankish Vita Fursei, and its overall validity is consequently dependent on the historical reliability of that text. The discussion argues that the Vita is reliable by correlating information it provides with independent Irish, Anglo-Saxon and Frankish sources. Of particular significance in this regard is the confirmation by geophysical evidence of the phenomenon of a darkening of the sun mentioned in the Vita and dated to the years 625/626 in the Irish Annals of Ulster.